Correction: Ecological footprints, global sustainability, and the roles of natural resources, financial development, and economic growth. - Ali Hussein Al-Marshadi; Muhammad Aslam; Azhar Ali Janjua (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0317664.].